(untitled) (Politeja, 2017)
Libertarianism and the Theory of Personal Identity. Robert Nozick’s Closest Continuer Theory as a Background Theory of the Principle of Self‑Ownership The research problem of the present paper is the following question: May the closest continuer theory serve as a background theory for the principle of self‑ownership? This issue is a peculiar instance of the more general problem of the anthropological presuppositions of the libertarian political philosophy that can be phrased in a Kantian manner: How is self‑ownership possible?; or in a more detailed way: What sort of entity a human being has to be, if it is possible for him to be a self‑owner? The research thesis that is argued for in the paper says that: 1) the closest continuer theory may not serve as a background theory for a wide principle of self‑ownership since as an example of reductionist theory of personal identity it excludes the possibility of possessing this set of psychological facts which the personal identity is reducible to and possession of which is presupposed by the wide principle of self‑ownership; 2) the closest continuer theory may though serve as a background theory for a narrow principle of self‑ownership since this principle assumes that one can own only scarce resources and psychological facts are not instances thereof.